Urea-modified candle soot for enhanced anodic performance for fast-charging lithium-ion battery application. (June 2020) - Gangadharan, Ananya; Mamidi, Suresh; Sharma, Chandra S.; Rao, Tata N.
Highlights: Urea is used as a fuel and porogen to modify candle soot carbon physiochemical properties. Urea modified candle soot exhibited enhanced electrochemical performance. A reversible capacity of 520 and 260 mAhg −1 at 5C and 10 C-rates after 900 and 2000 cycles respectively. Full cell delivered a high capacity (143 mAhg −1 ) at 50 mAg −1 with 312 Wh-kg −1 specific energy density. Urea modified candle soot as a binder free anode for high rate Li-ion batteries for electric vehicles. Abstract: We demonstrate a facile synthesis method to modify the candle soot morphology with the assistance of urea as a porogen during combustion to enable its use as a binder-free anode. As obtained urea modified candle soot varies significantly in its physical and electrochemical properties compared to candle soot deposited directly by burning the candle. While we characterize the physiochemical properties thoroughly in this work using X-ray diffraction, Raman spectroscopy, N2 adsorption/desorption isotherms, scanning as well as high resolution transmission electron microscopy, electrochemical properties of as-fabricated modified candle soot anode shows an outstanding specific capacity of 520 and 260 mAhg −1 at 5C and 10 C-rates after 900 and 2000 galvanostatic charge-discharge cycles respectively. Due to the presence of extra mesoporosity in the modified candle soot along with nitrogen doping from urea, electrochemical performance is significantly improved as compared to bare candle soot. Further, full cell studies show that as modified nitrogen-doped candle soot can deliver a high capacity of 143 mAhg −1 at 50 mAg −1 current density with 312 Wh-kg −1 specific energy density. Excellent electrochemical behavior of as-modified nitrogen doped candle soot reveals the potency of this material as an anode for Li-ion battery for high current applications such as hybrid electric vehicles.